MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN BAGI ANAK TUNAGRAHITA RINGAN KELAS III DI SLB MUHAMMADIYAH PAUH IX PADANG - Nadia Murni, Martias, Z, Rahmatrisilvi (Universitas Negeri Padang, 2013)
The research was backgrounded by the problem of that researcher found in ability of reading word with retardation mental needs in class III of junior high school special of school of Muhammadiyah Pauh IX Padang. The researcher want to prove that ability that the use of study aktive,innovative,creative,effective and fun can improve the ability in reading of child with retardation mental need. This research using single subject research approach the A-B-A design and data analysis techniques using visual analysis chart. Results of this study indicate that the study aktive, innovative, creative, effective and fun has improved the ability in reading of child with retardation mental in class III of junior high of special school of Muhammadiyah Pauh IX Padang